The importance of preoperative preparation of pediatric patients - Dušica Simić; Duygu Kara; Katarina Stančev; Ivana Budić; Ivana Petrov (Trends in Pediatrics, 2025)
Preoperative preparation is a complex series of steps aimed at establishing the conditions for selecting an individualized perioperative plan, bringing the child to the best possible state of health state, stabilizing higher-risk patients and reducing them to a lower-risk stage, informing parents about the type of anesthesia planned and the potential risks and complications, and minimizing parental anxiety. However, anticipation and the route to surgery create preoperative anxiety in children and their parents. Under conditions of increased stress, the child’s cooperativeness decreases, the requisite dosages of medications for premedication and induction increase, delirium may occur, and wound healing and recovery as a whole are prolonged. Sensitivity to pain also increases, leading to longer hospital stays and less satisfaction among patients and parents. Premedication is tailored to each patient based on age, body weight, health status, psychological profile, and the extent of the intervention. A thorough discussion with the anesthesiologist, a detailed examination, and an individualized anesthetic plan can minimize these effects. This paper describes pharmacological methods of preoperative preparation, provides recommended dosages, and draws attention to the potential side effects of the medications.